2009
DOI: 10.1002/bem.20486
|View full text |Cite
|
Sign up to set email alerts
|

Blood laboratory findings in patients suffering from self‐perceived electromagnetic hypersensitivity (EHS)

Abstract: Risks from electromagnetic devices are of considerable concern. Electrohypersensitive (EHS) persons attribute a variety of rather unspecific symptoms to exposure to electromagnetic fields. The pathophysiology of EHS is unknown and therapy remains a challenge. We hypothesized that some electrosensitive individuals are suffering from common somatic health problems. Toward this end we analysed clinical laboratory parameters including thyroid-stimulating hormone (TSH), alanine transaminase (ALT), aspartate transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…The ratio showed a remarkable elevation versus CTR in favor of the more proinflammatory ω 6 PUFA in the MCS group ( P < 0.001), while EHS values were instead nearly overlapping CTR values, data that appears consistent with the overall less pronounced prooxidative and proinflammatory state evidenced in EHS versus MCS, from the whole pattern of redox parameters investigated in this study. Again, this molecular marker difference between the two environmental hypersensitivities can possibly be connected with the clinical setting, where, for example, a higher frequency of pathological obesity with metabolic syndrome is observed in MCS [50], whereas EHS condition features a milder chronic inflammatory status [51]. …”
Section: Discussionmentioning
confidence: 99%
“…The ratio showed a remarkable elevation versus CTR in favor of the more proinflammatory ω 6 PUFA in the MCS group ( P < 0.001), while EHS values were instead nearly overlapping CTR values, data that appears consistent with the overall less pronounced prooxidative and proinflammatory state evidenced in EHS versus MCS, from the whole pattern of redox parameters investigated in this study. Again, this molecular marker difference between the two environmental hypersensitivities can possibly be connected with the clinical setting, where, for example, a higher frequency of pathological obesity with metabolic syndrome is observed in MCS [50], whereas EHS condition features a milder chronic inflammatory status [51]. …”
Section: Discussionmentioning
confidence: 99%
“…In a large-scale study, Bergamaschi et al detected no significant difference on the workers exposed to EMF because of cell phone use in terms of the TSH level; 59 Selmaoui et al found that low-dose EMF exposure for every other night or continuously did not affect serum total-free thyroxin (T4) and triiodothyronine (T3) as well as TSH levels. 60 No significant effect of low-dose EMF exposure for a long period was found on TSH in human studies carried out in a similar manner with less participation, 61 , 62 whereas no difference was detected on individuals exposed to low-density EMF for a long period in terms of the frequency of thyroid cancer. 63 Koyu et al found a significant decrease in T3, T4, and TSH levels in the rats who were exposed to a low-dose EMF for 4 weeks when compared with the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, there are very few data available on IEI-EMF's biomarkers [Dahmen et al, 2009;Ghezel-Ahmadi et al, 2010]. Further studies are needed to look for other biomarkers that may help in diagnosing IEI-EMF.…”
Section: Discussionmentioning
confidence: 99%